Characteristics of Synthesized Copper Oxide (CuO) Nanoparticles using Maize Husks: A Green Chemistry Approach - Abiola Olawale Ilori; Olanrewaju Ajanaku (Three E Science Institute, 2022)
Nanoparticles of a transitional metal oxide such as Copper (II) oxide or cupric oxide have gained considerable interest in the research and development community due to the corresponding conventional materials' extremely different characteristics. Hence, this study aimed at characterizing Copper (II) oxide nanoparticles synthesized through a direct green chemical approach using the outer leafy cover of the maize husk. The fresh maize husk's optical absorption spectrum shows broad peaks that were cantered around 209, 241, and 331 nm, which are the characteristic of flavonoids. The structural analysis shows the formation of Nantokite with a face-centered crystal structure, which has crystalline peaks (111), (220), (311), and (331) at 2θ = 28.5, 47.4, 56.28, and 76.6, respectively. In contrast, the spectrum of Copper (II) oxide showed a base-centred monoclinic crystal structure with lattice parameters: a= 4.688, b = 3.4229, c = 5.1319 and β = 99.91. In conclusion, nanoparticles' synthesis using aqueous corn husk extract was successfully synthesized and characterized. This environmentally friendly approach is a simple, environmentally friendly, inexpensive process and is reproducible.